Emergent feminisms complicating a postfeminist media culture - Keller, Jessalynn 1982- (Routledge Research in Gender, Sexuality, and Media, 2018)
"Through twelve chapters that historicize and re-evaluate postfeminism as a dominant framework of feminist media studies, this collection maps out new modes of feminist media analysis at both theoretical and empirical levels and offers new insights into the visibility and circulation of feminist politics in contemporary media cultures. The essays in this collection resituate feminism within current debates about postfeminism, considering how both operate as modes of political engagement and as scholarly traditions. Authors analyze a range of media texts and practices including American television shows Being Mary Jane and Inside Amy Schumer, Beyonce's "Formation" music video, misandry memes, and Hong Kong cinema. "--Provided by publisher